Romanian Journal of Indian Studies no. 8/ 2024 - GLIGOR, Mihaela (Presa Universitară Clujeană, 2024)
The Romanian Journal of Indian Studies seeks and encourages interdisciplinary approaches in linguistics, literature and literary studies, Indian philosophy, history of religions, political philosophy, and history of ideas, science, anthropology, sociology, education, communications theory, history, and performing arts. One of its primary aims is the integration of the results of the several disciplines of the humanities so that its studies will have a synthetic character in order to acquaint the reader with the progress being made in the general area of Indian Studies. The present issue of Romanian Journal of Indian Studies appears with the generous support of Ministry of Culture, Government of India, and Embassy of India in Romania.